(untitled) (INTERNATIONAL JOURNAL OF TECHNOPRENEURSHIP AND INNOVATION, 2024)
This paper examined the interdependence of actors, resources and activities in the innovation ecosystem. The aim is to understand the relationships and the value created between different actors. While the Triple Helix and Quadruple Helix are popular in innovation studies, the relations between them have not been addressed extensively in literature. To bridge the research gap, this paper compared the models from the perspective of how they were introduced and how useful they are in addressing the innovation processes in contemporary society. The findings and results indicated that the two models showed that they are complementary in value creation when analyzing innovation processes in the society. They provide ground for synergy building between the two Helix models. The research however, concluded that the fourth helix where societal value creation is generated by the dynamics in the relationships between academic industry and government and providing more value adding activities through society in a quadruple helix will enhance our understanding of the need for informed interactions of these innovation models through a strong civil society. This development has transformed the triple helix into the quadruple helix.